(untitled) - New, Michael B. (Rome, 1982)
This manual has been prepared on the basis of Thai experience in the farming of the giant freasrwater prawn Macrobrachium rosenbergii. It has a practical orientation, as it was written for extension and fishery officers as well as for practising,.......
Keywords: Shrimp culture,Macrobrachium rosenbergii